Heatline visualization of natural convection in a thick walled open cavity filled with a nanofluid - Bondareva, Nadezhda S.; Sheremet, Mikhail A.; Öztop, Hakan Fehmi; Abu-Hamdeh, Nidal (Pergamon-Elsevier Science Ltd, 2017)
Natural convection of an alumina-water nanofluid in a partially open rectangular cavity with a left heat conducting solid wall of finite thickness and conductivity has been studied numerically. Governing equations formulated in dimensionless stream function and vorticity variables on the basis of a single-phase nanofluid model with corresponding boundary conditions have been solved by finite difference method. Analysis of the influence of Rayleigh number (Ra =10(3)-10(6)), thermal conductivity ratio (1 <= K <= 20), solid wall thickness (0.1 <= delta <= 0.3) and nanoparticles volume fraction (0 <= phi <= 0.05) on streamlines, heatlines and isotherms as well as average Nusselt number at solid-fluid interface and fluid flow rate has been carried out. It has been revealed that for the considered models for an effective thermal conductivity ratio and dynamic viscosity an increase in the nanoparticles volume fraction leads to the heat transfer reduction and decrease of the fluid flow rate. (C) 2017 Elsevier Ltd. All rights reserved.
Keywords: Semi-open cavity; Heat-conducting solid wall; Natural convection; Nanofluid; Heatlines; Numerical results